-8y+6(y+7)=27

Simple and best practice solution for -8y+6(y+7)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8y+6(y+7)=27 equation:


Simplifying
-8y + 6(y + 7) = 27

Reorder the terms:
-8y + 6(7 + y) = 27
-8y + (7 * 6 + y * 6) = 27
-8y + (42 + 6y) = 27

Reorder the terms:
42 + -8y + 6y = 27

Combine like terms: -8y + 6y = -2y
42 + -2y = 27

Solving
42 + -2y = 27

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -2y = 27 + -42

Combine like terms: 42 + -42 = 0
0 + -2y = 27 + -42
-2y = 27 + -42

Combine like terms: 27 + -42 = -15
-2y = -15

Divide each side by '-2'.
y = 7.5

Simplifying
y = 7.5

See similar equations:

| 6(n+1)=2n-2 | | -7+49= | | 6[7+2(k-1)]-1=5 | | 5x-2-x/6=14 | | 6x-8=9x-3 | | y=14/2-4 | | 5x/2-x-6=14 | | 3/16=×/12 | | (1-9x)/5=-3x-7 | | y=0/2-4 | | C-7=6 | | -3=36 | | 4a-18=a | | y=-2/2-4 | | 3x+18=120 | | 6h-7d=29 | | y=-6/2-4 | | z/7-4=10 | | x^2+y^2-4x+8y+20=0 | | b+4.003=9 | | 2x-26=8x+13 | | 3(2x*4)+2=4x+50 | | 11(x+1)=20 | | Y=4x/5 | | 48/u=12 | | -10x-5+7x=45 | | 7x+8=5x-6 | | 34(21-6.5x)=16(6x-8)+49.5 | | 2a+5=a-2 | | 1/5-9×/5=3x-7 | | 9n=4-35 | | ln(x)=-1.71636 |

Equations solver categories